Mechanosensitive nuclear checkpoint: nuclear envelope as a sensor of chromosomal instability and driver of cell fate - Chenyang Ji; Junwei Chen; Fuxiang Wei (Mechanobiology in Medicine)
The nuclear envelope (NE) is a dynamic, mechanosensitive structure that functions as a protective barrier for the genome and serves as a checkpoint responding to external stimuli. It plays a critical role in maintaining genomic stability and regulating cell fate. This review synthesizes recent research highlighting the role of NE as a mechanical checkpoint in ensuring accurate chromosome segregation, regulating cell cycle progression, and contributing to cancer development. Chromosome mis-segregation during cell division is a major driver of aneuploidy, a condition closely associated with genomic instability and cellular transformation. The role of NE in chromatin organization and gene expression regulation is also discussed, underscoring its importance in cell differentiation and identity.